SOME FOREST TREES FOR HONEYDEW HONEY PRODUCTION IN TURKEY - Ünal, S.; Ayan, S.; Karadeniz, M.; Yer, E. N. (Publishing House SB RAS, 2017)
Honey is an important source of nutrients and energy and an effective remedy against various human diseases. Honeydew honey is produced from honeydew of phloem-feeders that honeybees gather. In this study, we focused on honeydew producers and diversity of host tree species which are involved in honeydew production in Turkey. A total of 24 honeydew producers by host tree species are identified in Turkey. Of these, 13 coniferous trees and 11 deciduous trees. The main honeydew producer in Turkey is a scale insect, Marchalina hellenica Gennadius (Hemiptera: Margarodidae) living mainly on pines (Turkish red pine, Aleppo pine, and rarely on stone pine, Anatolian black pine and Scots pine). Honeydew producer insects can be treated as serious pests of conifer and broadleaf trees. The aphids and the scale insects such as Ceroplastes floridensis, Cinara cedri, C. laportei, Eulachnus rileyi, Icerya purchase, Kermes vermilio, Lichtensia viburni and Saissetia oleae are known as pests in several European, Asian and African countries. Despite their potential harm to their host plants, insect species producing honeydew play an important role in honey production in Turkey. Turkish honey production is exported to EU countries and, furthermore beekeeping is an important part of agricultural sector in Turkey.
Keywords: Turkey; aphids and cochineals; Forestry; SD1-669.5; honeydew honey; forest trees; 2. Zero hunger; 15. Life on land; 3. Good health